Neural stem cell research - Greer, Erik V. (Nova Science Publishers, 2006)
Interactions between transplanted neural stem cells and host tissue: a two-way street / Teresita L. Briones -- Roles of extracellular matrix molecules in neural stem cell development and the example of tenascin-C / Jeremy Garwood -- Towards a molecular signature of neural stem cells / Martin H. Maurer and Wolfgang Kuschinsky -- To know neural stem properties from diseased brains: a critical step for brain repair / M. Fernández [and others] -- Neural stem cells and taurine / Eulalia Bazán [and others] -- Retrovirus vector silencing in stem cells / Shuyuan Yao and James Ellis -- Classification of cell phases in time-lapse images by vector quantization and Markov models / Tuan D. Pham [and others].
Includes bibliographical references and index